SYNERGY OF GREEN FINANCE AND MAQASID SHARIA: A STUDY OF THE DEVELOPMENT OF GREEN SUKUK IN INDONESIA - Lubis, Sopian; Windiana, Wiwin (Khatulistiwa, 2024)
This research explores the relationship between green finance and Maqasid Shariah through a study of the development of green sukuk in Indonesia. Green sukuk, as a Shariah-compliant financing instrument aimed at environmentally friendly projects, philosophically aligns with Maqasid Shariah, which emphasizes the protection of religion, life, intellect, lineage, and property. This study employs a qualitative method based on literature review to analyze the development of green sukuk since its first issuance in 2018. The findings indicate that green sukuk in Indonesia has shown significant growth, with an increase in issuances and funded projects, such as renewable energy and sustainable transportation. The implications of this research suggest that green sukuk not only contributes to sustainable financing but also strengthens the principles of Shariah within the context of modern Islamic finance. This study recommends an expanded green economic model based on Maqasid Shariah to support sustainable development policies in Indonesia.